Changes in Attitudes towards mental illness after exposure to a course in abnormal psychology among students of a Nigerian University (2007)
Background Several community studies in Nigeria of attitudes towards mental illness suggest low knowledge and a deep-seated negative attitude about the illness. Little is known about the effect of education in changing these rather negative views. Aims: To determine the effects of exposure to a 13 week course in Abnormal Psychology on a follow-up assessment of knowledge and attitudes of undergraduate students of the University of Ibadan, Nigeria towards mental illness. Method: All 140 students who registered for Abnormal Psychology: course code Psy 202 in the 2004/2005 academic session were first assessed at baseline (the first day of lecture) and at after 13 weeks (26 hours) the end of course evaluation. The response rate was 100% at both baseline and at follow-up. Results: At the follow-up evaluation, knowledge about mental illness was significantly higher in all the items measured. There were non-significant changes in all items assessing stigma of mental illness except in the items indicating feeling upset or disturbed working in the same job and maintaining a friendship with someone with mental illness respectively. A significant favourable change was observed in the students perception towards group homes in the neighbourhood for people with mental illness. No significant changes were observed in attitudes toward human rights of the mentally ill, except regarding an item stating that mentally ill individuals should not have children in order to avoid heredity handicaps, with which a lower percentage agreed. Conclusions: Poor knowledge and stigmatization of mental illness still exist among undergraduate students in Nigeria. While exposure to a course in abnormal psychology was effective in changing knowledge, there were still some aspects of stigma that were not amenable to education.